2022
DOI: 10.3390/machines10050368
|View full text |Cite
|
Sign up to set email alerts
|

Stress Characteristics Analysis of Vertical Bi-Directional Flow Channel Axial Pump Blades Based on Fluid–Structure Coupling

Abstract: The RANS equation and the RNG k-ε turbulence model were used in the three-dimensional non-constant numerical simulations of the full flow path of a vertical axial-flow pump which was carried out by applying CFX software. The velocity characteristics of the flow field and the pressure distribution of the impeller under different operating conditions were analyzed and verified by external characteristic tests. The fluid–structure interaction research was conducted for the stress distribution and deformation feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Concurrently, the temporal evolution of stress manifests a discernible periodic pattern. Simultaneously, scholars have undertaken investigations into the structural attributes of various pump devices, including the bidirectional flow channel axial flow pump device [14], the S-type front axle extended tube pump device [15], and full tube axial flow pump units [16]. Scholars have elucidated the stress and strain distribution in the pump device utilizing fluid-structure coupling methods, providing insights into potential crack locations.…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently, the temporal evolution of stress manifests a discernible periodic pattern. Simultaneously, scholars have undertaken investigations into the structural attributes of various pump devices, including the bidirectional flow channel axial flow pump device [14], the S-type front axle extended tube pump device [15], and full tube axial flow pump units [16]. Scholars have elucidated the stress and strain distribution in the pump device utilizing fluid-structure coupling methods, providing insights into potential crack locations.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the maximum deformation occurred at the blade rim, and the deformation gradually decreased along the edge from the leading edge (LE) to the trailing edge (TE). Liu et al [15] analyzed the stress and deformation of the blades of a vertical bi-directional axial-flow pump based on the flow field pressure distribution and found that the stress concentration occurred at the center of the connection between the blade root and the hub and the maximum stress value at stress concentration decreased with increasing flow rate. Shi et al [16] compared the equivalent stress distributions of an axial-flow pump and a full tubular pump and found that the maximum equivalent stress of an axial-flow pump was lower than that of full tubular pump under different flow conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al investigated the distortion mechanism of inlet fluid and the energy characteristics of the fluid in a bidirectional axial flow pump and found that the non-uniform inflow of the fluid negatively affected the efficiency and head of the pumping device [11]. This was because of the bidirectional axial flow pump's reverse operation on the structure of the impeller by the influence of the guide vane, showing different hydraulic performance [12,13]. Wang et al investigated the internal flow of a bidirectional axial pump and found that flow separation at the blade tails during reverse operation resulted in performance degradation [14].…”
Section: Introductionmentioning
confidence: 99%